2015
DOI: 10.1093/dnares/dsv005
|View full text |Cite
|
Sign up to set email alerts
|

Functional classification of 15 million SNPs detected from diverse chicken populations

Abstract: Next-generation sequencing has prompted a surge of discovery of millions of genetic variants from vertebrate genomes. Besides applications in genetic association and linkage studies, a fraction of these variants will have functional consequences. This study describes detection and characterization of 15 million SNPs from chicken genome with the goal to predict variants with potential functional implications (pfVars) from both coding and non-coding regions. The study reports: 183K amino acid-altering SNPs of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 62 publications
(88 reference statements)
6
55
0
1
Order By: Relevance
“…Four non‐synonymous SNPs of LEAP‐2 mature peptide region were reported in 243 chickens from 24 lines (Gheyas et al . ). However, these non‐synonymous SNPs include two frameshift mutations: the amino acid at position 48 changed from proline to serine, which is only found in proline residues in birds, and that at 75 changed from serine to proline, which is highly conserved in birds (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Four non‐synonymous SNPs of LEAP‐2 mature peptide region were reported in 243 chickens from 24 lines (Gheyas et al . ). However, these non‐synonymous SNPs include two frameshift mutations: the amino acid at position 48 changed from proline to serine, which is only found in proline residues in birds, and that at 75 changed from serine to proline, which is highly conserved in birds (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This could be attributed to the fact that these SNPs were very rare in birds, or to sequence error, which was analyzed by a next‐generation sequencer and included in two frameshift mutations (Gheyas et al . ). In the six strains of Japanese quail used in this study, it has been reported that there are polymorphisms in the CD1 (Yokoyama et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These variants include N174H and D466H, both found in the leucine-rich surface that is responsible for recognizing and binding double stranded viral RNA and activating innate immunity. When viewed in the context of other mutations that alter charge (D19V, K43Q, R266S, E283G), we hypothesize that the sensitivity of TLR3 to double stranded viral 14 components could be diminished. This decrease in functional efficacy could be physiologically important for growth performance, for example, a mouse knock out of a toll-like receptor (TLR5) has previously been shown to modulate gut microbiome characteristic of obesity and other metabolic disorders [39].…”
Section: Combinatorial Prioritization Strategy Identifies Candidate Gmentioning
confidence: 99%
“…Such sweeps have revealed the fixation of alleles predicted to be beneficial. For example, specific alleles of the gene encoding thyroid stimulating hormone receptor (TSHR), which is critical for proper metabolic regulation and reproduction, have been shown to be fixed in all modern chickens, but not in the genomes of the Red Jungle Fowl [10,13,14] or chickens dating from ~280 B.C. to ~1700 A.D [13].…”
Section: Introductionmentioning
confidence: 99%